Pengaruh Stres dan Konflik Kerja Terhadap Kinerja - Eka Susilowati; Gunistiyo; Roberto Akyuwen (ARBITRASE: Journal of Economics and Accounting, 2022)
The purpose of this study is to determine the effect of work stress and conflict on local government’s employee performance with gender as a moderator. The primary data was gathered from 80 respondents by using a closed questionnaire. These respondents were the employees of the Government of Tegal City. The collected data was analyzed using a single regression. The first conclusion is that work stress and conflict can affect employees’ performance. Secondly, it was found that gender is able to moderate the relationship between stress and work conflict and employees’ performance.